2009 IEEE Conference on Computer Vision and Pattern Recognition 2009
DOI: 10.1109/cvpr.2009.5206774
|View full text |Cite
|
Sign up to set email alerts
|

Learning optimized MAP estimates in continuously-valued MRF models

Abstract: We present a new approach for the discriminative training of continuous-valued Markov Random Field (MRF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 16 publications
(15 reference statements)
1
70
0
Order By: Relevance
“…We incorporate this data-driven regularization model into a standard Markov Random Field (MRF) model, inferred with a gradient descent algorithm [14] and learned with a discriminative learning approach [19]. Compared to prior state-of-the-art methods, our full model achieves comparable or better results on the KITTI stereo and flow datasets [7], and improves results on the Sintel Flow dataset [4] under an online estimation setting.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…We incorporate this data-driven regularization model into a standard Markov Random Field (MRF) model, inferred with a gradient descent algorithm [14] and learned with a discriminative learning approach [19]. Compared to prior state-of-the-art methods, our full model achieves comparable or better results on the KITTI stereo and flow datasets [7], and improves results on the Sintel Flow dataset [4] under an online estimation setting.…”
Section: Introductionmentioning
confidence: 96%
“…We do a grid search for λ S and below we describe the discriminative learning approach [19] to optimize {γ q }.…”
Section: Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In [32], Tappen trained FOE parameters by minimizing a loss function with stochastic gradient descent. Samuel and Tappen [23] presented an improved version based on implicit-differentiation. Li and Huttenlocher [18] presented a discriminative learning algorithm based on simultaneous perturbation stochastic approximation.…”
Section: Related Workmentioning
confidence: 99%
“…Since then however, a large body of work [21,34,36,38] has found that histograms of filter responses for natural images tend to be highly "nonGaussian", in that they have sharp peaks at zero and heavy tails. Consequently, recent works have focused on nonconvex priors [2,22,23,32,36].…”
Section: Introductionmentioning
confidence: 99%